1980
DOI: 10.1109/tac.1980.1102538
|View full text |Cite
|
Sign up to set email alerts
|

Failure of a parallel adaptive identifier with adaptive error filtering

Abstract: Stable adaptive controller d e s i @ IEEE T m . A u r o m .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In fact, it was shown in Ref. (15) that the minimum phase condition of D(q −1 , n) must also be satisfied in order to guarantee that e OE (n) converges to zero in the mean sense. This additional condition implies that a continuous minimum phase monitoring should be performed in the polynomial D(q −1 , n) to assure global convergence of the SHARF algorithm.…”
Section: Rementioning
confidence: 99%
“…In fact, it was shown in Ref. (15) that the minimum phase condition of D(q −1 , n) must also be satisfied in order to guarantee that e OE (n) converges to zero in the mean sense. This additional condition implies that a continuous minimum phase monitoring should be performed in the polynomial D(q −1 , n) to assure global convergence of the SHARF algorithm.…”
Section: Rementioning
confidence: 99%
“…This is achieved via an augmented parameterization. Johnson and Taylor subsequently pointed out [3] that, despite the asymptotic convergence of the a posterori adaptation error to zero, nothing could be said about the convergence of the a priori model error. This claim was supported by a suitably generated simulation example [3].…”
Section: Introduc~onmentioning
confidence: 99%
“…Johnson and Taylor subsequently pointed out [3] that, despite the asymptotic convergence of the a posterori adaptation error to zero, nothing could be said about the convergence of the a priori model error. This claim was supported by a suitably generated simulation example [3]. A partial answer to this problem was given in [4] where it was suggested that the adjustable compensator should be kept in a stability region by some form of projection procedure.…”
Section: Introduc~onmentioning
confidence: 99%